The Patient in Patient Safety: Unique Perspectives of Researchers Who are also Patients. Issue 1 (September 2020) - Papautsky, Elizabeth Lerner; Holden, Richard J.; Valdez, Rupa S.; Ernst, Katie; Kushniruk, Andre
In a panel format, four systems researchers who are also patients described their experiences navigating their care continuum in relation to human factors topics. Getting inside the heads of researcher-patients is an opportunity to elicit unique perspectives on healthcare, which may not be captured through research alone. Researcher-patients may navigate and observe their care continuum with a lens attuned to identifying research questions, as well as gaps and opportunities for interventions that support patients in health-related work, clinicians in decision making, and a culture shift towards effective patient-clinician teaming in service of improved safety and quality. We provide detailed recommendations, as well as a concise take-away tool intended for healthcare organizations.